Thermomechanical behaviour of refractory dry-stacked masonry walls under uniaxial compression. (1st August 2021) - Oliveira, Rafael L.G.; Rodrigues, João Paulo C.; Pereira, João M.; Lourenço, Paulo B.; Marschall, Hans Ulrich
Highlights: Experimental and numerical tests on dry-joint refractory masonry walls carried out. Tests carried out at ambient and high temperatures. Loadbearing capacity, cyclic loading and thermal restrained behaviour tested. Identified effects of stress concentration caused by brick's height imperfections. Concrete damaged plasticity model proved to be suitable in numerical modelling. Abstract: Vessels used in industrial high temperature processes of steel and cement production are protected by refractory linings built with dry-stacked masonry, which plays a crucial role on the overall behaviour of the vessels. This paper presents the results of an experimental and numerical research on dry-joint refractory masonry subjected to uniaxial compression. Its main purpose is to fully characterize the masonry walls at different temperatures and different loading conditions. Several aspects that may influence the behaviour of these walls have been tested, namely the loadbearing capacity, the behaviour under cyclic loading and the restrained thermal elongation. The experimental results allowed to identify the effects of the stress concentrations caused by brick's height imperfections in the mechanical behaviour of the bricks and in the loadbearing capacity of the specimens, the evolution of the wall's Young's modulus with the load application, the developed crack patterns and the mechanical behaviour of the samples at ambient and high temperatures. Numerical models were also developed to simulate the behaviour of the walls under different testing conditions and a good agreement with the experimental results was obtained. The concrete damaged plasticity model, using a micro-modelling approach, proved to be suitable for representing the behaviour of these walls at ambient and high temperatures.